Pengendalian Proyek Instalasi Pengolahan Lumpur Tinja Kota Pagar Alam - Diki Anggara; Masagus Taswin; Fameira Dhiniati (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2018)
: In this study analyzing the project control of the Pagar Alam City Sludge Treatment Plant (IPLT) using software ms. Project 2007. the extent of the effectiveness of the process of controlling time, labor, material and costs in the project. Analyzing critical work paths, Analyzing workforce needs, Analyzing material needs, Analyzing work costs and cash flow. Based on the results of the analysis using the software ms.project 2007 provides more efficient results than the previous work plan, time and cost of implementation of 180 calendar days at a cost of Rp. 4,175,352,000.00 - while the results of the analysis using software 2007 ms.project time and costs are used 124 calendar days with a cost of Rp. 2,910,421,890.